The Performance of the Land Agency in Issuing Certificates in Banjar Regency - Adwin Tista; Tomi Oktaviannor; Taufik Arbain (Publikasi Indonesia, 2026)
In issuing certificates in Banjar district and determine the supporting and inhibiting factors in the performance of land agencies in issuing certificates in Banjar district. The research method used in this research is a qualitative descriptive method with a geetz interpretive model approach, namely a phenomenological approach that seeks to find meaning and not look for laws, understand each problem and not look for theories of phenomena. The research resulting is the performance of land agencies in issuing certificates in Banjar district is still less than optimal, because officials still expect compensation from applicants; there is discrimination among officials in providing services because of the proximity system; Responsiveness is still lacking due to complaints about making measuring drawings and land plot maps; Accountability is not good because there are many public concerns /complaints, there is no transparency regarding the costs and time of issuing certificates. The supporting factors for the performance of the land agency in issuing certificates in Banjar district are: discipline, public service vehicles for land certificates (LARASITA), computerized systems, waiting rooms, information boards, land flow charts and the existence of a complete system land registration program (PTSL). The factors inhibiting the performance of the land agency in issuing certificates in the city of Banjar district are human resources, lack of public understanding, lack of computer infrastructure, low capability of the apparatus, lack of coordination of the apparatus, inadequate storage of certificates, no funds to replace lost certificates, no guarantee of security.